Experiences of nurses in managing HIV and Tuberculosis in rural clinics, South Africa - Tokwe, Lwandile; Jordan, Portia; Marie Modeste, Regis (Health SA = SA Gesondheid, 2025)
Background: Globally, an estimated 40.8 million people were living with Human Immunodeficiency Virus (HIV) in 2024, with approximately 8.15 million reported in South Africa by 2025. Pulmonary tuberculosis (PTB) remains a prevalent opportunistic infection among people living with HIV. There is a paucity of research on the experiences of professional nurses in managing HIV and PTB co-infection. Aim: This study aimed to explore and describe the experiences of professional nurses in managing newly diagnosed patients living with HIV and PTB co-infection in the rural primary health care (PHC) clinics. Setting: The research was conducted in Mthatha, Eastern Cape province, South Africa. Methods: A qualitative research approach with an exploratory, descriptive and contextual design was used. Data were gathered from 11 professional nurses through semi-structured interviews, which were audio recorded, transcribed, and analysed using Tesch’s eight-step method. Results: Three themes emerged, with Theme 1, exploring the roles of professional nurses in managing HIV and PTB co-infection. Theme 2, delved into the challenges experienced in managing this co-infection. Lastly, Theme 3 focused on the support structures that facilitated the care provision of patients. Conclusion: The HIV and PTB co-infection affects people globally. Tailored interventions are needed to support clinicians, especially professional nurses, in managing HIV and PTB co-infection and improving care for newly diagnosed patients. Contribution: This study provides insights into the experiences of professional nurses in managing newly diagnosed patients living with HIV and PTB co-infection. It further expands the knowledge on health care interventions adopted by professional nurses to promote the health of these patients.